How Dictionary Users Choose Senses in Bilingual Dictionary Entries: An Eye-Tracking Study - Lew, Robert; Grzelak, Marcin; Leszkowicz, Mateusz (Lexikos, 2013)
We use modern eye-tracking technology to scrutinize the process of sense and equivalent selection in polysemous bilingual entries. Our study subjects, intermediate and advanced Polish learners of English, consulted 26 Polish-to-English dictionary pages prompted with a sentence translation task. Throughout the task, an eye-tracking device unobtrusively recorded their gaze patterns, which are analyzed and discussed. Both successful and unsuccessful searches are examined. Also, we assess the potential of eye-tracking technology in the study of dictionary use.